Validity of narrow-band imaging (NBI) nasoendoscopy on nasopharyngeal carcinoma post therapy biopsy - Herdini, Camelia; Heriwiyanto, Bambang; Yendri, Veby Novri (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Nasopharyngeal carcinoma (NPC) is the most common malignancy found in the head and neck. It is a unique head and neck cancer due to its radiosensitivity. Therefore, radiotherapy becomes the main modality of therapy. Post-treatment evaluation of NPC is important to assess prognosis. Biopsy that is the gold standard for the evaluation can be performed with a narrow-band imaging (NBI) nasoendoscopy guide. This study aimed to determine the validity of NBI nasoendoscopic examination of NPC post-treatment biopsy. This study was a cross-sectional design for all post-treatment NPC patients who would undergo response assessment at the Department of Otorhinolaryngology, Head and Neck Surgery, Dr. Sardjito General Hospital, Yogyakarta. A total 40 patients during May-June 2018 period who underwent examination sequentially. Biopsy examination was carried out with NBI nasoendoscopy guidance and the results of biopsy were performed histopathological examination. Forty patients showed the results of NBI nasoendoscopic validity on NPC biopsy after treatment included sensitivity (85.7%), specificity (87.8%), positive predictive value (60%), negative predictive value (96.6 %), positive trend ratio (7.07), negative trend ratio (0.16), and accuracy (87.5%). Postoperative NBI nasoendoscopy features appear homogeneous (75%) and inhomogenous (25%). In conclusion, NBI nasoendoscopic validity on postoperative NPC biopsy is good.